Inoculation of greenhouse tomato (Solanum lycopersicum L.) cv. afrodita with plant growth-promoting rhizobacteria - Espinosa Palomeque, Bernardo; Moreno Reséndez, Alejandro; Cano Ríos, Pedro; Álvarez Reyna, Vicente de Paul; Sáenz Mata, Jorge; Sánchez Galván, Homero; González Rodríguez, Gabriela (REVISTA TERRA LATINOAMERICANA, 2017)
Production of agricultural crops is affected by weather, soil, water, and microorganisms in the rhizosphere, among other factors. Of these factors, plant growth-promoting rhizobacteria (PGPR) have important functions, such as the production of plant growth regulators and reduction or prevention of effects of pathogenic microorganisms. The objective of this study was to evaluate the effect of inoculating greenhouse tomatoes with three PGPR: Bacillus spp., Aeromonas spp., and Pseudomonas lini Delorme, using two substrates: 1) compost+river sand+perlite; and 2) river sand, and as controls both substrates without PGPR (T1-T8), on fruit yield and quality. The experimental design used was completely randomized blocks with five replicates in a 2 × 4 factorial arrangement, the factors were: A) substrates and B) PGPR. The evaluated variables in fruit were polar and equatorial diameter, pericarp thickness, content of soluble solids, firmness, total phenols and antioxidant capability, as well as total yield. The data were statistically analyzed through analysis of variance and comparison of means with the DMS test, 0.05%. The fruits from treatment T1 (50 compost + 40 river sand + 10 perlite + Bacillus) had the highest values in polar and equatorial diameters, content of total soluble solids, firmness, total phenol content, and antioxidant capability: 6.54 cm, 5.50 cm, 5.94 ºBrix, 12.54 N, 51.70 mg AG 100 g-1 FF, and 66.68 µM Trolox g‑1 FF, respectively. Application of PGPR and use of the compost based substrate could constitute alternative fertilization for greenhouse tomato production to increase yield and nutraceutical quality of the fruits without inorganic fertilizers.